Effect of calcination and carbon incorporation on NiO nanowires for photodiode performance - Soylu, M.; Dere, A.; Al-Sehemi, Abdullah G.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier, 2018)
We report the effect of calcination and carbon (C) incorporation on the characteristic properties of nickel oxide (NiO) consisting of nanowires. The identification of NiO is carried out at room temperature using X-ray diffraction (XRD) and Raman spectroscopy. The images of NiO nanowires are investigated by scanning electron microscope (SEM). It has been observed that the morphology is affected by calcination and carbon incorporation. The optical band gaps vary in the range of 3.22 to 3.42 eV. NiO-based heterojunction is obtained by inserting nanowire structured NiO layer between Al electrode and Si. NiO/p-Si heterojunction shows rectifying behavior in the dark and exhibits prominent photovoltaic response under light. The photovoltaic performance of the NiO/p-Si isotype heterojunction diode is significantly changed with calcination and carbon (C) incorporation of NiO. Results imply that the characteristic properties of NiO as transparent electrode can be improved by doping and calcination for efficient optoelectronic applications.
Keywords: NiO; Calcination; Electrical properties